Conditional Factors Associated with Behaviors for Preventing Relapse of Major Depressive Disorder in The Older Persons: Perspectives of Older Persons who had Remission and Non-Relapsed of Major Depressive Disorders and Their Relatives - Saima-in, Hathairat; Jinnge, Prateep; Surakarn, Amaraporn; Peungposop, Narisara (Journal of The Royal Thai Army Nurses, 2024)
The objective of this research was to study and understand conditional factors associated with behaviors for preventing relapse of major depressive disorder in the older persons, namely self-efficacy for coping with depression, stressful life events, expressed emotion of family members, other factors that supportive and obstacles. This research was qualitative research by case study design with research participants are older persons who remission and non-relapsed of major depressive disorder 6 persons and their relatives 6 persons, total 12 persons. Data were collected through in-depth interviews, and recorded the interview speech, and the data were analyzed using content analysis. The research results found that the perspectives of the older persons and their relatives on the conditional factors associated with behaviors for preventing relapse of major depressive disorder in the older persons is divided into 2 parts; Part 1: psychosocial factors associated with behaviors for preventing relapse of major depressive disorder in the older persons referring to 3 main factors: 1) Self-efficacy for coping with depression 2) Stressful life events 3) Expressed emotion of family members. Part 2: other factors that supportive and obstacles to the behaviors for preventing relapse of major depressive disorder in the older persons are include emotional and mental aspects, knowledge and information aspects, and economics aspects. It is knowledge for the development of tools and programs to enhance the behavior of preventing relapse for older patients with major depressive disorder in the further.